Desain Vending Machine Jas Hujan menggunakan Finite State Automata - Irvan Yuniar M; Windu Gata; Okky Robiana Sulaeman; Suwanda Aditya Saputra; Bobby Suryo Prakoso (Institut Bakti Nusantara, 2022)
Based on BMKG since 1981-2018 rainfall intensity in Indonesia ranges from 1, 20, 50, and 100 mm/day in a year. Conditions like this are quite difficult for drivers of two-wheeled vehicles, especially in the middle of a long journey. Raincoats are the only tool that can be used for riders to continue their journey safely and comfortably. Finite State Automata is the method used to describe the behavior of vending machine (VM) using state events, events, and actions.VM simulation design for raincoat sales. There are two kinds of raincoats available at VM Poncho raincoats and top-down raincoats. Based on the results of the FSA design and simulation, it can be concluded that the finite state automata can be used as the basis of logic to perform VM design and simulation. State diagram design based on FSA machine concept, the input results selected by the customer in accordance with the design results.